2016
DOI: 10.1039/c6dt00782a
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide metal–organic frameworks as selective microporous materials for adsorption of heavy metal ions

Abstract: Four microporous lanthanide metal-organic frameworks (MOFs), namely Ln(BTC)(H2O)(DMF)1.1 (Ln = Tb, Dy, Er and Yb, DMF = dimethylformamide, H3BTC = benzene-1,3,5-tricarboxylic acid), have been used for selective adsorption of Pb(ii) and Cu(ii). Among these MOFs, the Dy-based MOF shows better adsorption property and selectivity toward Pb(ii) and Cu(ii) ions. Adsorption isotherms indicate that sorption of Pb(ii) and Cu(ii) on MOFs is via monolayer coverage. Preconcentration is based on solid-phase extraction in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 132 publications
(44 citation statements)
references
References 53 publications
(58 reference statements)
4
37
0
3
Order By: Relevance
“…Several factors such as electrostatic interactions, covalent interaction, size and shape of the pores, etc. can have an effect on the selectivity of adsorption . One typical example is functionalization of unsaturated Cr 3+ metal centers of ultra‐stable MIL‐101(Cr) by ethanediamine.…”
Section: Selectivity Toward Target Metal Ionssupporting
confidence: 85%
See 1 more Smart Citation
“…Several factors such as electrostatic interactions, covalent interaction, size and shape of the pores, etc. can have an effect on the selectivity of adsorption . One typical example is functionalization of unsaturated Cr 3+ metal centers of ultra‐stable MIL‐101(Cr) by ethanediamine.…”
Section: Selectivity Toward Target Metal Ionssupporting
confidence: 85%
“…can have an effect on the selectivityo fa dsorption. [42] One typical example is functionalization of unsaturated Cr 3 + metal centers of ultra-stable MIL-101(Cr) by ethanediamine. After grating, the adsorption capacity of MIL-101(Cr) for Pb 2 + showed that the four-fold increase and the selectivity for Pb 2 + compared with otheri ons, such as Zn 2 + ,Co 2 + ,C u 2 + ,a nd Ni 2 + was greatlyi mproved.…”
Section: Selectivity Toward Target Metal Ionsmentioning
confidence: 99%
“…Adsorption capacity of 1 for Pb 2+ and Cd 2+ is calculated after 30 min using the below equation (Eq. : truenormalQe=(C0-Cnormale)normalV/normalm4pt …”
Section: Resultsmentioning
confidence: 99%
“…[23] Moreover, some studies were carried out on the adsorptive properties of these coordination polymers. [24] In the continuation to our field of research in the synthesis of coordination polymers with adsorptive properties, [25] here we have reported a new coordination polymer, [Ce 2 (m 3 -atp) 2 (m 2atp)(H 2 O) 8 ].4H 2 O (1), and investigated the adsorptive properties of it for the removal of Cd 2 + and Pb 2 + from water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation